2018
DOI: 10.7150/jca.27381
|View full text |Cite
|
Sign up to set email alerts
|

OIP5 Promotes Growth, Metastasis and Chemoresistance to Cisplatin in Bladder Cancer Cells

Abstract: Opa interacting protein 5 (OIP5) has previously been identified as a tumorigenesis gene. The purpose of this study is to explore the role of OIP5 in the progression of bladder cancer (BC). The OIP5 expression and clinical behaviors in bladder cancer were collected from lager database. Our study showed that OIP5 was highly expressed in bladder cancer tissues and cells. Overexpression of OIP5 in tumor patients predicted worse overall survival (OS) and higher histological grade. Vitro and vivo experiments demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
2
8
0
1
Order By: Relevance
“…OIP5 is also known as Miss18β, that plays a critical role in centromere formation during the G1 phase (165,166). In accordance with this knowledge, OIP5 is an independent risk factor for BCR (HR, 1.94; 95% CI, 1.20-3.12; P=0.00638) after adjusting for age at diagnosis, GS, surgical margin and tumor stage (156); OIP5 promotes bladder cancer metastasis and chemoresistance (167), glioblastoma metastasis (168), it displays a biomarker potential in clear cell renal cell carcinoma (169), and it is upregulated in colorectal and breast cancer (170,171).…”
Section: Gene Expression-based Biomarkerssupporting
confidence: 59%
“…OIP5 is also known as Miss18β, that plays a critical role in centromere formation during the G1 phase (165,166). In accordance with this knowledge, OIP5 is an independent risk factor for BCR (HR, 1.94; 95% CI, 1.20-3.12; P=0.00638) after adjusting for age at diagnosis, GS, surgical margin and tumor stage (156); OIP5 promotes bladder cancer metastasis and chemoresistance (167), glioblastoma metastasis (168), it displays a biomarker potential in clear cell renal cell carcinoma (169), and it is upregulated in colorectal and breast cancer (170,171).…”
Section: Gene Expression-based Biomarkerssupporting
confidence: 59%
“…OIP5 was found to be highly expressed in many types of cancer. Studies have confirmed its role in the progression of hepatocellular, bladder, and gastric cancers 35–37 . Interestingly, OIP5 was also recognized as a downstream gene of E2F1 in the tumorigenesis and metastasis of glioblastoma, 38 which is consistent with the GSEA enrichment to E2F target in our study (Figure S3A,B).…”
Section: Discussionsupporting
confidence: 89%
“…Chemotherapy is an important treatment for BC, and cisplatin is considered to be the first-line chemotherapy for advanced BC [ 83 ]. However, due to drug toxicity and heterogeneity among patients, 40–60% of patients with bladder cancer do not respond to cisplatin-based systemic chemotherapy [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%